Agrourbanism Tools for Governance and Planning of Agrarian Landscape - Gottero, Enrico (GeoJournal Library, 2019)
This book provides a much needed overview of the agrourbanism topic in the context of territorial studies. It carefully looks at rural, urban, periurban farming in both professional and unprofessional capacities as one of the main sustainable forms of land use and management. This cutting edge text explores the various forms of agricultural and urban planning, as well as the main innovations that the agro-urban approach entails in terms of governance, spatial dimensions and functions. Agrourbanism provides a breadth of information and serves as a practical study of concerns facing policy and decision makers, planners and landscape managers, as well as farmers, managers of protected areas, local authorities and local action groups. As such this book is suitable as a course accompaniment to provide an overview of the complexity of agro-urban issues.